Helle Virkner: En moderne statsministerfrue - Kunstmann, Kirstine (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2025)
This study investigates Helle Virkner’s role as First Lady to the Danish Prime Minister Jens Otto Krag (1962-1972) – a role that was not fully established at Virkner’s time. The study examines how she formed and modernized the role of the First Lady through her actions, media awareness, and strategic staging. The analysis is divided into a private and public part based on Virkner’s memoirs and contemporary newspaper and magazine articles. The study investigates Virkner’s perception of the role, the press’ framing, and public expectations. While fulfilling traditional duties, Virkner also challenged them through her active societal engagement and strategic media use. The press portrayed her through gendered stereotypes and Americanized ideals. Judith Butler’s theory of performativity and Lisa M. Burns’ concepts of framing and feminization are introduced in the discussion to bring a new perspective on Virkner’s role as First Lady. The theories explain how her actions reproduce and challenge contemporary gender norms. The study concludes that Virkner was a central actor in defining the Danish First Lady balancing tradition and modernity while reshaping public perceptions of women’s roles. Her political influence was greater than previously assumed contributing to Krag’s successes and marking her as Denmark’s first modern First Lady.